Genome sequencing of pancreatic cancer: differential expression by location. Issue 2 (31st January 2021) - Bi, F; Qian, Y; Song, L; Qu, H; Zheng, J; Fang, X; He, T; Yan, H
Abstract : The results demonstrated that pancreatic ductal carcinoma (PDAC) of the body/tail was associated with more transcriptional and genomic changes, and correlated with worse prognosis, than PDAC of the pancreatic head. The different mutation types and gene expression of tumour locations provide deep insight into the carcinogenesis or metastasis of PDAC, and suggest different early diagnostic and therapeutic strategies. SNV, single-nucleotide variations; NLS, Nuclear localization sequence; MB, million base-pairs; UTR, untranslated region.